Framgångsfaktorer för trygghetsboende. En utredning av olika aktörers inställning i trygghetsboendefrågan - Holmqvist, Hanna; Papp, Sofie (My University, 2013)
Assisted living is a relatively new form of housing that received a government definition in 2007 in conjunction with a government appointed investigation of future alternative accommodation for senior citizens. The type of accommodation is intended for seniors who have the need for increased security, which may be a consequence of that they feel anxious or lonely. It concerns ordinary homes with qualities that suit needs of seniors. There is no allowance from the local municipality required in order for seniors to apply for these homes and so assisted living should not be confused with nursing homes/ sheltered housing. The purpose of this study is to identify success factors for a winning concept for assisted living in the Gothenburg region, on behalf of Skanska Project development. The thesis is geographically limited to look into the attitude of different parties regarding assisted living in the Gothenburg region. The focus is therefore on parties such as the municipality of Gothenburg, municipal and private housing companies operating within the Gothenburg region. The result of the thesis is based largely on interviews with the different parties. Most of them have a positive attitude towards assisted living but it appears that the municipalities currently possess most knowledge in the subject area. The commitment however varies greatly both between municipalities and between parties. Case studies in the form of two visits have been carried out in order to give an idea of what type of accommodation is portrayed and how the proposed business works. Whether the Swedish term for assisted living should be replaced to clarify the meaning and to attract the target audience, for marketing purposes, is discussed. Furthermore the future situation of the construction of assisted living including location, type of ownership and accountability is also discussed. The conclusions of the thesis includes an array of identified success factors assessed on six aspects: value for the end customer, the needs of seniors and their willingness to pay, project development companies´ negotiating opportunities, criteria for assisted living, municipalities' willingness to provide subsidies and economic security and feasibility. Based on the identified success factors it is estimated that a concept should have two approaches since the target group, the seniors, have different needs and lifestyles. The first approach should have focus on nursing and care aspects. The second one should focus on the value-added aspects in addition to accessibility and security. For the convenience of the contractors during the construction of assisted living, there must be more uniform building codes and criteria. In addition, cooperation between parties is a key factor for a successful outcome. The conclusions also include recommendations for further studies.
Keywords: Samhällsbyggnadsteknik; Building Futures; Civil Engineering; Building Futures